MENINGKATAN HASIL BELAJAR SISWA MELALUI PENGGUNAAN METODE DEMONSTRASI DENGAN MEDIA POTONGAN LIDI PADA PELAJARAN MATEMATIKA DI KELAS 1 SEMESTER 2 UPT SD NEGERI 068344 MEDAN TUNTUNGAN - Lubis, Nuraini (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2021)
The purpose of this study was to improve learning outcomes by using the demonstration method with stick stick media for Class 1 Semester 2 students at SD Negeri 068344 Medan Tuntungan in 2019/2020. This research uses Kurt Lewin's classroom action research method. The main concept of Kurt Luwin's classroom action research includes four components, namely planning, acting, observing and reflecting. The research subjects were first grade students of SD Negeri 068344 Medan Tuntungan, Medan City, for the 2019/2020 academic year, consisting of 14 students consisting of 07 male students and 07 female students whose abilities in learning were heterogeneous. The research instruments used to collect data in this classroom action research are observation sheets conducted during learning activities and learning outcomes tests to measure student learning outcomes in cognitive aspects or the level of mastery of the subject matter. Giving the demonstration method with cutting stick media to grade 1 students can improve learning outcomes in mathematics. This can be seen from the results of observations during learning activities by students, the results obtained from cycle I and cycle II are: 66% and 82%. The results of filling out the learning outcomes instrument on the subject of arithmetic operations, addition and subtraction of numbers obtained from 14 students, then 02 students completed while 12 people did not complete in the first cycle and in the second cycle 14 students all completed.